DIGITAL EYES: HOW OPTICS AND MATHEMATICS TEACH ARTIFICIAL INTELLIGENCE TO SEE - Khusiddinov Fakhriddin Shamsiddinovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article provides a comprehensive analysis of the concept of digital eyes, focusing on the role of optics and mathematical modeling in teaching artificial intelligence to see. Based on historical and modern theories, global and regional research, and practical applications, it highlights the formation, developmental stages, and current challenges of artificial vision systems. Special attention is given to theoretical and practical approaches, critical analysis, and prospects, offering a holistic overview of scientific, programmatic, and technological advancements in the field of digital eyes.